Incidence and risk factors for syphilis infection among men who have sex with men: A cohort study from an urban sexual health clinic in Jakarta, Indonesia. (October 2022) - Kawi, Nurhayati H; Sihotang, Erik P; Nisa, Tiara; Hui, Ben; Causer, Louise M; Januraga, Pande Putu; Ronoatmodjo, Sudarto
Objective: Syphilis infection remains a significant health issue among marginalised populations in Indonesia, in particular among men who have sex with men (MSM), in whom there are limited studies from Indonesia exploring risk factors associated with STI acquisition.Our study aimed to identify risk factors of syphilis infection among MSM attending large sexual health clinic in Jakarta.Methods: We conducted a retrospective cohort analysis using patient records (MSM aged 18 years or older) period Jan 2018-Dec 2019. We used Cox regression to identify risk factors associated with syphilis incidence.Results: Study population were 2912 MSM tested for syphilis, 473 (16.2%) were diagnosed with syphilis on their first visit; early syphilis (415; 14%) and latent syphilis (58, 2%). Among the cohort of 2439 MSM who tested negative at baseline, 40 MSM were identified with a new positive syphilis result during 2 years follow up. Risk factors remaining significantly associated with syphilis incidence included having STI symptom at 1st visit (aHR, 2.8; 95% CI, 1.38–5.65), and HIV-infection (aHR 4.53; 95% CI 2.24 – 9.17).Syphilis incidence rate was 8.19 (95% CI 6.01-11.16) per 100 PYFU.Conclusions: Syphilis infection at baseline and incidence was high among MSM attending this large clinic in Jakarta. Integrated and accessible syphilis prevention and detection coupled with HIV services are needed, with a special focus on high-risk individuals.